PENGARUH PERTUMBUHAN PENJUALAN, UKURAN PERUSAHAAN DAN STRUKTUR MODAL TERHADAP PERUBAHAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DIBURSA EFEK INDONESIA - Margiani, Farida - (EKONOMIA, 2019)
The study aims to determine and analyze whether sales growth, firm size and capital structure affect the changes in earnings in Manufacturing Companies in Indonesia Stock Exchange. The data used in this study is secondary data sourced from the financial statements of manufacturing companies in 2013-2015 obtained from the official website of the Indonesia Stock Exchange is www.idx.co.id.The method used in this research is descriptive method. Of the 432 registered company population in the manufacturing company, 46 samples of companies were obtained that met the test criteria. So that the amount of data to be analyzed amounted to 138. Before performing the data analysis techniques, first tested the classical assumption. Hypothesis testing using multiple linear regression test by performing F test and t test.The result of partial research shows that Sales Growth variable has significant effect to Profit Changes, with a significance value of 0,000 smaller than 0.05; Firm Size variable has no significant effect on Profit Change, with a significance value of 0.547 bigger than 0.05; and the variable of Capital Structure have no significant effect to Profit Change, with value of significance 0,241 bigger than 0,05. Simultaneously shows that Sales Growth, Firm Size and Capital Structure variables significantly influence Profit Change, with a significance value of 0.001 smaller than 0.05.